Attitude and Knowledge of Third-Trimester Pregnant Women toward Labor Anxiety in New Normal Covid-19 Era at Puskesmas Abiansemal I - Primadewi Kadek (Gaster, 2023)
Introductory summary: Pregnant women can become stressed as a result of feelings of fear and anxiety experienced by pregnant women in excess which will have an impact on pregnancy and the delivery process. Objective: To determine the relationship between attitudes and knowledge of third trimester pregnant women about anxiety in dealing with the new normal era of Covid-19 labor at the Abiansemal I Public Health Center. Methods: This study used a correlational quantitative method, with total of 62 pregnant women. Respondents were taken by total sampling. The level of knowledge and attitude was measured by a questionnaire from Putranti and the level of anxiety was measured using the HARS questionnaire, then tested by the Spearman Rank method. Results: The results obtained from 62 respondents is 36 respondents (60%) were obedient in consuming TTD. 58 respondents (93.5%) had good knowledge and 59 respondents (95.2%) had moderate level of anxiety. The results showed p-value = 0.955 (p>0.05) on knowledge with a correlation of -0.135 and p-value = 0.297 (p>0.05) on attitudes with a correlation of -0.007. Conclusion: There is an insignificant relationship between knowledge and attitudes of pregnant women toward labor during the new normal covid-19 era at Abiansemal I Health Center.